DIAGNOSTICS OF LEARNING DIFFICULTIES OF GRADE 4 STUDENTS AT STATE PRIMARY SCHOOL 61 BANDA ACEH - Nola Fajria; Siti Mayang Sari; fitriani Manurung (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Diagnostics of learning difficulties is one way that can be used to study andunderstand the problems experienced by students in teaching and learningactivities. This research aims to determine students' learning difficulties inschool subjects and the factors causing them. This research is included in thedescriptive research type using a quantitative approach. The population of thisstudy were students at State Elementary School 61 Banda Aceh consisting of164 people. Meanwhile, the research sample was 29 class IV students. The datacollection technique used was a questionnaire and analyzed using descriptivepercentage techniques. The research results show that; (1) The “Very Difficult”subject is Mathematics with a percentage of 44.82% (2) Lessons in the"Difficult" category are Pancasila Education with a percentage of 41.37%Religious Education is a "Not Difficult" subject with a percentage of 96.55%and PJOK is also considered "Not Difficult" because the percentage is 89.65%.The conclusion of this research is that every fourth grade student at SD Negeri61 Banda Aceh experiences learning difficulties, this is caused by internalfactors such as low interest in learning something. And external factors, namelythe learning methods used by teachers do not match the characteristics ofstudents.